Korelasi Antara Outgoing Longwave Radiation (OLR) dan Total Precipitable Water (TPW) di Wilayah Indonesia Periode 1996 - 1999 - Juniarti Visa; Iis Sofiati; Teguh Harjana (Indonesian Journal of Physics, 2002)
Analysis of four years (1996-1999) of the monthly mean of outgoing longwave radiation (OLR) and total precipitable water (TPW) obtained from satellite NOAA 12, 14 data over Indonesia, was done with the software TeraScan Vers.2.6 and a 2.0° × 2.5° grid. From the results, the value of OLR of Indonesia is about (220 - 340) W/m2 and TPW about (40 - 60) mm. It was found that OLR and TPW are negatively correlated. South of the Equator the value is higher (-0.8), and we suspect that this condition is influenced by the North Australia Indonesia-Monsoon. At the North West of Indonesia the correlation coefficient is lowest (- 0.4), and we suspect this condition is influenced by the South East Asia Monsoon.